Sistema de gestión de alertas. INA- CIRSA - Catalini, Carlos G.; Rico, Andrea F.; Dasso, Clarita M.; Capone, M. Eugenia; Mortarino, Nadia (2024)
Fil: Catalini, Carlos G. Instituto Nacional del Agua-Centro de la Región Semiárida; Argentina.